FLAVOR-CHANGING NEUTRAL CURRENTS IN SU(3)L-CIRCLE-TIMES-U(1)Y MODELS - Dumm, D. G.; Pisano, F.; Pleitez, Vicente [UNESP] (World Scientific Publ Co Pte Ltd, 1994)
We consider flavor changing neutral current effects coming from the Z' exchange in 3-3-1 models. We show that the mass of this extra neutral vector boson may be less than 2 TeV and discuss the problem of quark family discrimination.